(untitled) (ETIMA, 2021)
Abstract E-learning is becoming an increasingly common form of teaching process. It is most often used in holding courses, seminars, conferences, and similar lectures, but it can also be effectively implemented for the teaching process in high schools and colleges. The increase in demand for tools that would enable this process also raises the development of concepts and practical solutions to these problems. A number of tools and services are available for the practical realization of e-learning. An important aspect of these solutions is data security and privacy. Implementation approaches and policies are individual to the providers of such services. But not completely. However, they are also subject to legal regulations. Within the European Union, the GDPR (General Data Protection Regulation) privacy policy is in force, which obliges private companies to have an ethical attitude towards the user data they own. In essence, this regulation calls for transparency. In that sense, the company must clearly state what type of user data it has, how it collects it, how it protects its privacy and for what purpose it uses it. The user must be notified of this in a timely manner and give his consent. Additionally, if the user requests a report at any time and for any reason for the data that the company has about him, the company is obliged to submit it. If the company does not offer such transparency to customers in the European Union, it may be subject to legal sanctions. Because online services generally operate worldwide, these privacy policies are widely accepted, and because of the good ethical practice they imply, some companies implement them for users around the world. This paper will analyze 4 potential e-learning software solutions: ZOOM, Microsoft Teams, BigBlueButton and BlueJeans. An overview of their general functionalities, policies and functionalities within the security, policies, and functionalities within the protection of user data privacy, as well as the GDPR compliance of each of these platforms will be given. Keywords: cyber security, e-learning, videoconference, GDRP compliance